URGENSI BAHASA ARAB DALAM PENDIDIKAN DAN BUDAYA ISLAM DI PULAU SERIBU MASJID (LOMBOK) - Abu Haif; Ali Fathurrahman; Noor Aziziah Bt. Adam; Baiq Raudatussolihah (Universitas Muhammadiyah Makassar, 2025)
This study aims to examine the importance of Arabic in the development of Islamic education and culture on the Island of a Thousand Mosques, the nickname for Lombok Island, which is famous for its numerous mosques and the religious life of its people. Arabic, as the language of the Qur'an, plays a central role in strengthening religious understanding, improving the quality of Islamic education and culture, and shaping the Islamic identity of the local community. This study used a qualitative approach with in-depth interviews and field observations in several Islamic boarding schools and madrasas on Lombok Island. The results show that mastery of Arabic not only functions as a means of religious communication but also as a main pillar in the process of internalizing Islamic cultural values. Arabic has proven to be the main medium for studying yellow books, reading the Qur'an, and character education based on Islamic educational and cultural values.